Zakat distribution and Islamic human development: a sequential explanatory study - Nilasari, Widiyanti Ayu; Mamduh, Muhammad Faizul; Setianingsih, Hesti Eka; Awaludin, Azrul Afrillana; Cholil, Muhammad; Widiastuti, Tika; Ali, Mohammad Mahbubi (Department of Islamic Economics, Pascasarjana, IAIN Kudus, Indonesia., 2025)
This study examines the impact of zakat distribution across five key sectors; education, health, humanitarian, economic, and da'wah, on the Islamic Human Development Index (IHDI) in Indonesia from 2015 to 2022. Employing a sequential explanatory design, quantitative data were analyzed using regression techniques, followed by qualitative insights from focus group discussions with zakat management institutions. The findings reveal significant positive effects of zakat distribution in the economic and humanitarian sectors on IHDI improvement. While the da’wah and health sectors exhibit negative effects, possibly due to a short-term orientation that limits measurable development outcomes. The education sector shows an insignificant impact, highlighting the need for long-term strategies. This study provides policy recommendations to optimize zakat distribution for sustainable human development, emphasizing productive utilization aligned with the principles of maqasid al-shariah (objectives of Islamic law).